PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS NASABAH BANK (STUDI KASUS PADA BCA CABANG DUTA MAS JAKARTA) - Tiofany, Annie; Wahyoedi, Soegeng (Manajemen Bisnis Kompetensi, 2008)
The advance of new technology and strict competition in banking industry have forced the management to continually improve their services. Improvement in quality of service is expected to increase customer loyalty. The purpose of this case study was to provide information to top level management, regarding service quality level of BCA Cabang Duta Mas Jakarta. The descriptive-verification method was used to explore the service quality level and the relation of service quality to customer loyalty in this bank. This study found that there was a low-positive correlation between service quality and customer loyalty.Keywords: service quality, customer loyalty, descriptive-verification